1992
DOI: 10.1111/j.1471-6402.1992.tb00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Linkages Between Women's Provider-Role Attitudes, Psychological Well-Being, and Family Relationships

Abstract: The primary aim of this investigation was to examine the extent to which the meanings women attach to their provider‐role responsibilities are differentially related to their psychological well‐being and family relationships and to the division of labor in the home. The sample included 43 dualearner and 50 single‐earner families. In home interviews, wives reported on role overload, depression, satisfaction with the marriage, and attitudes regarding women's and men's roles. Their children completed two measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 23 publications
5
50
2
Order By: Relevance
“…Income may only increase wives' power under some circumstances (Blumstein & Schwartz, 1991). For instance, Perry-Jenkins, Seery, and Crouter (1992) found that husbands of women who identified themselves as coproviders, viewing breadwinning as a responsibility that husbands and wives should share equally, spent more time completing household tasks than did husbands of homemakers and women who viewed their income as helpful but not essential.…”
Section: Prominent Theoriesmentioning
confidence: 95%
“…Income may only increase wives' power under some circumstances (Blumstein & Schwartz, 1991). For instance, Perry-Jenkins, Seery, and Crouter (1992) found that husbands of women who identified themselves as coproviders, viewing breadwinning as a responsibility that husbands and wives should share equally, spent more time completing household tasks than did husbands of homemakers and women who viewed their income as helpful but not essential.…”
Section: Prominent Theoriesmentioning
confidence: 95%
“…For example, several studies have found that coprovider wives are more educated and earn more than wives espousing main-secondary attitudes (Helms-Erikson et al, 2000; Perry-Jenkins et al, 1992; Potuchek, 1992; 1997). Although similar patterns emerged in income and education for husbands’ provider role groups, mean differences were not statistically significant in the only study that examined variation based on husbands’ provider role attitudes (Perry-Jenkins & Crouter, 1990).…”
Section: Provider Role Attitudes and Human Capital Investmentsmentioning
confidence: 99%
“…According to provider role research, employed women fall into four categories: co-provider, primary provider, secondary provider, or ambivalent provider (Perry-Jenkins and Crouter 1990;Perry-Jenkins et al 1992). While provider roles reflect justifications for employment and provide insight into women's perceptions of their employment roles, there is still considerable overlap between provider roles, number of employment hours, and perceived choice to work; that is, primary and co-providers are typically employed full-time, secondary providers are employed part-time, and ambivalent providers perceive no choice in their employment decision (c. f. Perry-Jenkins and Crouter 1990;Perry-Jenkins et al 1992).…”
Section: Introductionmentioning
confidence: 99%